2017
DOI: 10.1534/g3.117.044255
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-Wide Transcriptional Dynamics in the Companion Bacterial Symbionts of the Glassy-Winged Sharpshooter (Cicadellidae: Homalodisca vitripennis) Reveal Differential Gene Expression in Bacteria Occupying Multiple Host Organs

Abstract: The agricultural pest known as the glassy-winged sharpshooter (GWSS) or Homalodisca vitripennis (Hemiptera: Cicadellidae) harbors two bacterial symbionts, “Candidatus Sulcia muelleri” and “Ca. Baumannia cicadellinicola,” which provide the 10 essential amino acids (EAAs) that are limited in the host plant-sap diet. Although they differ in origin and symbiotic age, both bacteria have experienced extensive genome degradation resulting from their ancient restriction to specialized host organs (bacteriomes) that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 74 publications
2
6
0
Order By: Relevance
“…These patterns are in line with the transcriptomes of obligate endosymbionts in other insect groups, where genes coding for chaperones and host-beneficial factors (e.g. essential amino acids) are among the most highly expressed 41 . But given the symbiont’s extracellular localization within its host and during transmission, 7 , we aimed to quantify the symbiont’s transcriptional plasticity relative to host development and nutritional requirements.…”
Section: Resultssupporting
confidence: 77%
“…These patterns are in line with the transcriptomes of obligate endosymbionts in other insect groups, where genes coding for chaperones and host-beneficial factors (e.g. essential amino acids) are among the most highly expressed 41 . But given the symbiont’s extracellular localization within its host and during transmission, 7 , we aimed to quantify the symbiont’s transcriptional plasticity relative to host development and nutritional requirements.…”
Section: Resultssupporting
confidence: 77%
“…Within the M. mongolica / Sulcia integration, most genes related to the biosynthesis of EAAs were highly expressed (FPKM >100) in all the samples, no matter whether they were samples of nymphs or adults (Figure 6; Table S8), which suggest the highly produced EAAs of Sulcia in all cicada life stages. This is congruent with genome‐wide transcriptome level gene expression estimates of Sulcia in the glassy‐winged sharpshooter Homalodisca vitripennis (Bennett & Chong, 2017). The expression pattern of genes related to the biosynthesis of EAAs supports the prediction that the genome of Sulcia encodes pathway genes for most essential amino acid biosynthesis for the host insects (Matsuura et al, 2018; McCutcheon & Moran, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…Our annotation also revealed that genes related to protein folding and stability are shared throughout, including the GroES-GroEL chaperonin complex and the bacterial heat shock protein 70 (Hsp70) (Figure S1A). Suggestive of an important role in the biology of bacterial symbionts [33], such chaperones are among the most highly expressed enzymes within the bacteriomes of aphids [34], cicadas [35], tsetse flies [36], sharpshooters [37], and leaf beetles [11]. In contrast, pathways for the synthesis of essential amino acids, cofactors, and lipids are missing, as are genes encoding signal transduction, cell surface structures, and motility (Figure 2; Data S1).…”
Section: Resultsmentioning
confidence: 99%